Володимир Вернадський і сучасність (до 150-річчя від дня народження та 25-річчя заснування Комісії з розробки наукової спадщини академіка В.І. Вернадського НАН України) - Ситник, К.М.; Андріанова, Т.В. (Український ботанічний журнал, 2013)
В статье, посвященной 150-летию со дня рождения академика
В.И. Вернадского, дан обзор его деятельности, рассмотрены
научные связи ученого с Украиной. Показана актуальность
положений Владимира Вернадского о планетарном значении растительного покрова и всего живого, изложенных им
биогеохимических принципов, а также принципов государственности и профессиональности академии, необходимости развития широкого комплекса наук для прогресса общества. Представлен краткий очерк деятельности Комиссии
по разработке научного наследия академика В.И. Вернадского НАН Украины и развития идей ученого в Украине. The article devoted to the 150th anniversary of Academician V.I. Vernadsky’s
birthday, provides a review of his activities and his links
with Ukraine. It is emphasized that many statements of Vladimir
Vernadsky become topical, such as global significance of vegetation
and living matter, his biogeochemical principles, and the
concept of the public status and professionalism of the Academy,
relevance to develop a wide range of sciencies for progress. It is
proposed an overview of functioning of the Comission for Study
of Academician V.I. Vernadsky Heritage of the NAS Ukraine and
development of Vernadsky’s ideas in Ukraine.